Synthesis of Large, Stable Colloidal Graphene Quantum Dots with Tunable Size - Yan, Xin; Cui, Xiao; Li, Liang-shi (Journal of the American Chemical Society, 2010)
We report a solution-chemistry-based approach to large, stable colloidal graphene quantum dots with uniform size and shape. The versatility of solution chemistry allows us to tune the structures of the graphenes and thus their properties.